Analisis Laporan Arus Kas (Studi Kasus PT. Bosua Asuransi Cabang Jambi Bulan Oktober-Desember Tahun 2018) - Rezagi Meilano; Heriyani; Almizon (LP2M Politeknik Jambi, 2023)
This study aims to determine the condition of cash flow in PT. Bosowa Insurance Jambi Branch. if you look at the analysis of the cash flow statement. Data collection is carried out with literature and documentation research techniques. Research methods. by using descriptive analysis methods using cash flow from operating activities, investments, and funding as well as ratio analysis, namely: Operating Cash Flow Ratio (AKO), Cash Coverage Ratio to Current Debt (CKHL), Capital Expenditure Ratio (PM), Total Debt Ratio (TH). The results of this study show that the company's total cash flow during October-December 2018 shows that the company is in a non-liquid condition when assessed in terms of its operational activities. With the ratio analysis that has been carried out, it can be concluded that there is a decrease in cash flow, especially in operating activities every year and the company's ability to overcome its current liabilities still cannot be resolved.This shows that Bosowa Asuransi Jambi Branch was in a bad position during October-December 2018